2010
DOI: 10.1007/s11259-010-9430-1
|View full text |Cite
|
Sign up to set email alerts
|

Airway responsiveness measured by barometric plethysmography in guinea pigs

Abstract: Barometric plethysmography has become an increasingly used method to indirectly measure respiratory function in unrestrained freely-moving animals. This technique has been criticized because of physiological uncertainty of its major index, the enhanced pause (Penh). Moreover, a recent study raises concerns that during histamine challenges part of the Penh response could be produced by upper airways (nasal) responses. In this study we compared airway responsiveness measured by barometric plethysmography and tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…In sum, although guinea pigs as all mammals in hypoxia appear to have an increased ventilation to metabolism ratio (i.e., hyperventilate in relation to metabolic needs), it would appear that in our experimental conditions (temperature and duration of hypoxia) such hyperventilation would be minimal, but if any, it would be generated exclusively by a decrease in O 2 consumption due to the unresponsiveness of their CB to hypoxia. This abnormal response of guinea pigs, in comparison to other mammals, prevents us from reporting the impact of CS and CSCH on chemosensitivity Literature on the value of Penh as a measure of airways resistance is divided, with some authors been attached to it (Bergren, 2001;Lomask, 2006) and some others neglecting its value (Flandre et al, 2003; for a recent discussion on the significance of Penh please see Vargas et al, 2010). Yet, in present study there are several findings that predicting an increase in airways resistance did indeed cause an increase in Penh values, and vice versa.…”
Section: Penh Values and Bronchiolar Wall Structurementioning
confidence: 99%
“…In sum, although guinea pigs as all mammals in hypoxia appear to have an increased ventilation to metabolism ratio (i.e., hyperventilate in relation to metabolic needs), it would appear that in our experimental conditions (temperature and duration of hypoxia) such hyperventilation would be minimal, but if any, it would be generated exclusively by a decrease in O 2 consumption due to the unresponsiveness of their CB to hypoxia. This abnormal response of guinea pigs, in comparison to other mammals, prevents us from reporting the impact of CS and CSCH on chemosensitivity Literature on the value of Penh as a measure of airways resistance is divided, with some authors been attached to it (Bergren, 2001;Lomask, 2006) and some others neglecting its value (Flandre et al, 2003; for a recent discussion on the significance of Penh please see Vargas et al, 2010). Yet, in present study there are several findings that predicting an increase in airways resistance did indeed cause an increase in Penh values, and vice versa.…”
Section: Penh Values and Bronchiolar Wall Structurementioning
confidence: 99%
“…Perhaps the most used parameter in barometric plethysmography is Penh, a unitless index that has been employed as a surrogate of lung resistance and airway obstruction [24,25]. We found that Penh in rabbits had a progressive decrease in the first 60 min of recording.…”
Section: Discussionmentioning
confidence: 75%
“…A potential limitation of our study is that validity of barometric plethysmography, and especially Penh, has been questioned by some authors [26,27]. However, this last parameter has proved to be correlated with acute changes in lung resistance during a cholinergic challenge in some animal species such as guinea pigs and mice [24,25]. Thus, barometric plethysmography seems to be an appropriate tool to measure acute modifications of pulmonary mechanics, such as those expected to occur during confinement of rabbits inside the plethysmograph box.…”
Section: Discussionmentioning
confidence: 89%
“…It is plausible that in this time frame, between drug administration and lung assays, the differences in the magnitude of the response could be counteracted. Likewise, Penh is a controversial parameter that not always correctly reflects airway resistance in guinea pigs (37). Factors, such as lung compartmentalization, pharmacokinetics, and pharmacodynamics of BAY 41-2272, administered orally, should be taken into account to determine their efficacy in the airway.…”
Section: Discussionmentioning
confidence: 99%